(untitled) (Research, Society and Development, 2022)
With the arrival of the new coronavirus, several health challenges were triggered. In addition to respiratory symptoms, patients affected by the disease may also present oral manifestations. Among the most common oral manifestations are dysgeusia, ulcers and candidiasis. It is up to the dental surgeon to recognize these manifestations, always establishing the best diagnosis and treatment for each case. The objective of the present work is to describe the main manifestations and oral consequences of COVID-19, investigating how often they occur and which places in the oral cavity they most affect. For data analysis, a descriptive research was used, using a theoretical framework with a qualitative approach. The search was carried out through PubMed, Scielo, VHL, Google Scholar and RSD Journal databases, using as descriptors: “COVID-19”, “oral manifestations”, “oral mucosa”, “dentists” and “SARS-CoV-2”. The presence of the dental surgeon is highly relevant within the multidisciplinary team in cases of coronavirus, as in addition to having several oral manifestations, its causes are also varied, requiring special attention for each case.